The impact of periodontitis on vascular endothelial dysfunction - Li, Qian; Ouyang, Xiangying; Lin, Jiang (Frontiers in Cellular and Infection Microbiology, 2022)
Periodontitis, an oral inflammatory disease, originates from periodontal microbiota dysbiosis which is associated with the dysregulation of host immunoinflammatory response. This chronic infection is not only harmful to oral health but is also a risk factor for the onset and progress of various vascular diseases, such as hypertension, atherosclerosis, and coronary arterial disease. Vascular endothelial dysfunction is the initial key pathological feature of vascular diseases. Clarifying the association between periodontitis and vascular endothelial dysfunction is undoubtedly a key breakthrough for understanding the potential relationship between periodontitis and vascular diseases. However, there is currently a lack of an updated review of their relationship. Therefore, we aim to focus on the implications of periodontitis in vascular endothelial dysfunction in this review.